Prospecting for l-arabinose/d-xylose symporters from Pichia guilliermondii and Aureobasidium leucospermi - da Silva, Ronivaldo Rodrigues [UNESP]; Prista, Catarina; Dias, Maria Conceição Loureiro; Boscolo, Mauricio [UNESP]; da Silva, Roberto [UNESP]; Gomes, Eleni [UNESP] (Springer Nature, 2020)
With the strong trend toward sustainable technologies, such as the gradual substitution of fossil fuel consumption, improvement in the utilization of sugars from lignocellulosic biomass appears to be an alternative for bioenergy. However, from a number of C5 sugars, few are used in fermentative processes for ethanol production. One of the reasons is because wild-type Saccharomyces cerevisiae is unable to efficiently co-utilize hexoses and pentoses via specific transporters for each type of sugar. Thus, a system of pentose uptake that is not modulated by d-glucose is required. Here, we were able to identify the presence of sugar/H+ symporters for d-xylose and l-arabinose, especially for Pichia guilliermondii, where an uptake of d-glucose via symporter was not detected. The best d-xylose uptake route in P. guilliermondii exhibited a KM of 48 mM and VMAX of 0.48 mmol h−1 g−1 at the early stationary phase (24 h). For l-arabinose, the best route of uptake exhibited a KM of 109 mM and VMAX of 0.8 mmol h−1 g−1 on log phase (12 h). The highest kinetic uptake was observed when the final pH of the medium was below 7. In general, an alkaline medium limited the expression of symporters. The results obtained in this study will help in the further investigation of these symporters through their overexpression in engineered S. cerevisiae.
Keywords: Bioenergy; Bioethanol; Fermentation; Pentose uptake; Yeast